A solution to price-based unit commitment using Lagrange relaxation combined with particle swarm optimization - Soriano, Rafael V.
This paper uses a new approach in solving the price-based unit commitment problem based on the Lagrange relaxation method combined with the particle swarm optimizations algorithm. In the case of a deregulated market system, a generating company's objective is to maximize its profit. The proposed method aids the generating company in arriving at an optimal solution that determines how much power and reserve are to be sold to the market and what generation schedule results in maximum profit. Simulated results are compared with published results obtained using other methods. The results show that solving the price-based unit commitment problem using Lagrangian relaxation combined with particle swarm optimization, successfully incorporates the constraints in the problem. The particle swarm optimization algorithm is able to optimized the economic dispatch and therefore reduces the cost of generation and maximizes profit for the generating company.